MOTIVASI KERJA PEGAWAI DI KANTOR CAMAT - Noprianus Hendro E.42008042 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This Paper writing slated to know about style and leadership quality on Camat's Office Gorged, in givesand increase job Motivation on Camat's Office Clerk Gorged after quality and performance in give service tosociety and Region progress. In application motivates not only of someone or of side outer (ekstrinsik) , but also ofthyself (intrinsik) . On this paper researcher works through about how Camat's leadership attitude in motivate itsclerk, and how increases clerk job motivation in works at Camat's Office Gorged. Formula about problemobservational it is how application motivate lead to clerk at Gorged Office. Thus, to the effect of observational it issubject to be know lead motivation application to clerk at Camat's office Gorged. This research utilize kualitatif'sapproaching by methodics descriptive research. This observational location at Camat's Office Gorged GorgedRegency. Subjek is research is Camat, sekcam, Kasi / kasubbag and staff at Camat's Office Gorged. Conclusion inobservational it that motivates that given by Camat's lead just fine, Although extant many constraints namely thereare some oknum reducing clerk is ardour in working, on clerk work relation is still less congruity, and onPrasarana's facility and Medium Camat's Office Gorged. with so as down clerk job motivation. Therefore ofchairman of Camat can give that motivation is working with every consideration. This observationalrecommendation for to the fore it noticed by clerk work relation, prasarana's medium and the better facility again.Key word: Camat's office Gorged, Application Motivates Lead and Motivation of its Clerk, Prasarana's mediumand Office Facility.